The 9th girl - Hoag, Tami (Dutton, Published by the Penguin Group, 2013)
Minneapolis investigators Sam Kovac and Nikki Liska find themselves in pursuit of a serial killer whose latest victim is a bullied adolescent who desperately sought a normal life.